Odious praise : rhetoric, religion, and social thought - MacPhail, Eric (The Pennsylvania State University Press, 2022)
"Reassesses the genre of epideictic rhetoric from antiquity to the Renaissance by looking at a series of texts that exploit the potential of praise to undermine consensus and to challenge the normative values of society. The authors covered range from Isocrates, Plato, and Aristotle to Erasmus, Machiavelli, and Montaigne"--